Efek Penambahan Multivitamin pada Pakan Terhadap Pertumbuhan dan Rasio Konversi Pakan Ikan Nila Nirwana (Oreochromis Niloticus) - Muhammad Nurul Amin Usman; Rusli Rusli; Sri Wahidah (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Increasing the growth of tilapia can be done by improving the quality of feed by adding multivitamins in the right amount. The purpose of this study was to determine the right dose of multivitamins for the growth and feed conversion ratio of nirvana tilapia (O. niloticus) in the biofloc system. This study was conducted from February to April 2024. This study used nirvana tilapia seeds measuring 4-5 g, with 5 treatments and 4 replications, namely 0 ml / kg of feed (control), 10 ml / kg of feed, 20 ml / kg of feed, 30 ml / kg of feed, 40 ml / kg of feed. The data was analyzed first using normality and homogeneity tests, then the data was analyzed using the analysis of variance test and the Least Significant Difference (LSD) further test. The results of the study showed a significant effect of multivitamin doses on the growth and feed conversion ratio of nirvana tilapia in the biofloc system, the optimal dose of multivitamins on the growth and feed conversion ratio of nirvana tilapia in the biofloc system was 40 ml/kg of feed with an absolute weight of 6.38 g, a specific growth rate reaching 1.53% and a feed conversion ratio of 1.08.